2023
DOI: 10.3390/jcm12206482
|View full text |Cite
|
Sign up to set email alerts
|

Activity Following Total Hip Arthroplasty: Which Patients Are Active, and Is Being Active Safe?

Laura Elisa Streck,
Yu-Fen Chiu,
Sebastian Braun
et al.

Abstract: Background: Younger and physically active patients demand a return to sport after total hip arthroplasty (THA). However, because of the risk of implant wear and loosening, high-impact activities are often not recommended. The current study evaluates predictive factors and revision rates in patients with higher activity levels. Methods: This retrospective study included 4152 hips in 3828 patients aged 45–75 that underwent primary THA for primary osteoarthritis between 2009 and 2019 with a minimum follow-up of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…One report indicated that some patients desire returning to a level of athleticism achieved only prior to the onset of OA [18]. The evolution of implant designs have led to fewer surgeon-recommended activity and sports restrictions following THA [19], with evidence that high activity is associated with improved implant survival [20,21]. Despite this, many patients report self-imposed activity restrictions due to anxiety regarding injury or damage to implants, rather than limitations associated with joint pain post-operatively [19,22].…”
Section: Introductionmentioning
confidence: 99%
“…One report indicated that some patients desire returning to a level of athleticism achieved only prior to the onset of OA [18]. The evolution of implant designs have led to fewer surgeon-recommended activity and sports restrictions following THA [19], with evidence that high activity is associated with improved implant survival [20,21]. Despite this, many patients report self-imposed activity restrictions due to anxiety regarding injury or damage to implants, rather than limitations associated with joint pain post-operatively [19,22].…”
Section: Introductionmentioning
confidence: 99%